Uniform Domain Name Dispute Resolution Policy: What Is It? - Rusli, Hardijan (Pelita Harapan University, 2003)
Internet domain names raise some unique trademark issue. One of the important issue is the interface between domain names and trademarks. A mark comprised of an internet domain name that does not function as an identifier of the source of goods or service cannot be regarded as a trademark or service mark. Domain names principally are not the same thing as marks and are used for many purposes other than the identification of a producer or seller of goods or services. Domain names function is mainly as connection facilitation between computers through the Internet but now it seems that there is another function of domain names, because of their easy-to-remember and human friendly form, domain names have become to constitute business or personal identifiers (First WIPO Internet Domain Name Process: Archive, http://wipo2.wipo.int/processl/, 3/17/03). Businesses have come to realize the significant potential of an internet web site as a means for providing information and offering goods or services directly to the consumer public. The domain name, because of its purpose of being easy to remember dan to identify, often carries an additional significance which is connected with the name or mark of a business or its product or sevices. Domain names as business or enterprise identifiers have come into conflict with trademarks. The potential for conflict inherent in the two different systems of registration has been exploited by persons who have made it a practice to register the trademarks of other persons or enterprises as domain names for themselves (